THE IDIOMATIC EXPRESSIONS USED BY THE CHARACTERS AS FOUND IN MEGAMIND MOVIE - Bielqis Elfath (Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2021)
The researcher discussed about The Idiomatic Expressions Used by The Characters as Found in Megamind movie. The movie has theme of heroic stories, in the dialogue it is found that the contain of idiomatic expressions, the movie storyline was good, has a good language structure and the movie contain the message that